KOMITMEN ORGANISASI STUDI KAUSAL MOTIVASI BERPRESTASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI DOSEN DI UNIVERSITAS MUHAMMADIYAH (UMMI) KOTA SUKABUMI - Muhammad Ichsan (Jurnal Manajemen Pendidikan, 2010)
This study aims to solve existing problems at the University The problem that occurs is thought to still lower organizational commitment lecturer at the University of Muhammadiyah Sukabumi caused by the low achievement motivation factors and job satisfaction among faculty. Therefore, the causal approach and method of the survey are expected to increase the degree of organizational commitment of the lecturers at the University of Muhammadiyah Sukabumi. This research was conducted diUniversitas Muhammadiyah Sukabumi for three months, from May 2010 until July 2010. The research concludes the research hypothesis is accepted and implies: (1) there is a significant direct effect on organizational commitment, achievement motivation, (2) the existence of a significant direct effect of job satisfaction lecturer on organizational commitment, (3) there is a significant direct effect on achievement motivation job satisfaction; increase in the degree of organizational commitment and positive impact on university lecturers.